BURIAL TAPHONOMY OF HUMAN REMIANS INTERRED IN IRON COFFINS FROM THE RHEM VAULT, NEW BERN, NORTH CAROLINA - Freakley, Kate (My University, 2024)
By investigating the burial taphonomy of human remains, we gain a better understanding of the important biological processes that take place following a person’s death. Taphonomy is the study of how organic materials pass from the biosphere to the lithosphere through processes such as decomposition, burial, and fossilization. This investigation focused specifically on iron coffin burials, which became popular during the Civil War (1861-1865), and their effect on the preservation of human remains in above ground burials. The first part of this study consisted of examining eight subadult skeletons to create an inventory of the present bones and note the taphonomic changes that occurred. The second part of the investigation used X-Ray Fluorescence (XRF) to conduct both a qualitative and a quantitative analysis of the elemental composition of the bone surface, soft tissue, and coffin materials. This provided further insight on whether there is a positive correlation between some taphonomic changes, such as red-colored staining of the remains and iron oxidation of the iron coffins. In addition, XRF analysis was used to identify any chemical signatures of embalming, such as arsenic. Establishing results of postmortem processes will help to further understand the effects of decomposition within iron coffins, which is essential knowledge in the fields of forensics and anthropology.
Keywords: Human burial taphonomy; iron coffins; X-Ray Florescence Analysis